Photo-Induced Drug Release from Polymeric Micelles and Liposomes: Phototriggering Mechanisms in Drug-Delivery Systems - Salkho, Najla (2022)
Chemotherapeutic drugs are highly effective in treating cancer. However, the side effects associated with this treatment lower the quality of life of cancer patients. Smart nanocarriers are able to encapsulate these drugs to deliver them to tumors while reducing their contact with the healthy cells and the subsequent side effects. Upon reaching their target, the release of the encapsulated drugs should be carefully controlled to achieve therapeutic levels at the required time. Light is one of the promising triggering mechanisms used as external stimuli to trigger drug release from the light-responsive nanocarriers. Photo-induced drug release can be achieved at a wide range of wavelengths: UV, visible, and NIR depending on many factors. In this review, photo-induced release mechanisms were summarized, focusing on liposomes and micelles. In general, light-triggering mechanisms are based on one of the following: changing the hydrophobicity of a nanocarrier constituent(s) to make it more soluble, introducing local defects within a nanocarrier (by conformational transformation or photo-cleavage of its lipids/polymers chains) to make it more porous or concentrating heat for thermo-sensitive nanocarriers to release their payload. Several research studies were also presented to explore the potentials and limitations of this promising drug release triggering mechanism.